The Tax Treatment of Losses: Options for Reforms During the Corona Crisis - Reinald Koch; Dominika Langenmayr (Wirtschaftsdienst)
Abstract Due to the corona pandemic, many companies will suffer losses in 2020. The German tax system treats profits and losses asymmetrically: Whereas profits are taxed immediately, losses do not generate immediate tax refunds. This article discusses different options to improve the tax treatment of companies in loss situations. A microsimulation of these reforms reveals that extending the maximum amount for loss carry-back has a larger impact than extending the loss carry-back period. Enhancing loss carry-back opportunities also creates strong investment incentives.